The Legitimacy Conflict of the Sapta Rsi Javanese Priest in Sidoarjo, East Java: Socio-Religious Analysis of Community Service and Institutional Recognition - Subakti, I Made; Adi, I Wayan Arsiawan; Putra, I Ketut Abadi (Sphatika: Jurnal Teologi, 2025)
This article examines the legitimacy conflict experienced by the Sulinggih of Sapta Rsi Jawa, specifically Romo Rsi Hasto Dharmo Eko Telabah, in providing spiritual guidance to the Hindu community in Indonesia. Despite having actively and widely provided religious services with an approach rooted in Javanese tradition, formal recognition from the local Parisada Hindu Dharma Indonesia (PHDI) has not yet been fully obtained. This qualitative research utilizes data from questionnaires distributed to East Javanese Hindu figures, digital footprints, and literature reviews, with a focus on the textual analysis of the Lontar Siwa Sasana and sociological perspectives on authority. The findings indicate that the aguron-guron (discipleship) and diksa (initiation) processes of Sapta Rsi Jawa, which differ from the standard procedures of the PHDI, are the root of the issue. On the other hand, the community feels a tangible benefit from the services of Sapta Rsi Jawa, which fill a void in spiritual guidance by imparting local wisdom. This article concludes that there is a clash between the charismatic-traditional legitimacy possessed by Sapta Rsi Jawa and the bureaucratic-legal legitimacy held by the PHDI. The recommendation proposed is the necessity for dialogue, mediation, and the application of the Desa Kala Patra principle to achieve harmonization for the benefit of the entire Hindu community.